Evaluasi Water Shut Off Dan Membuka Lapisan Baru Sumur Bagong Di Lapangan Lesma - Abdullah Rizky Agusman; Aly Rasyid; Dika Latief Lesmana (Jurnal Bhara Petro Energi, 2023)
Evaluation of Water Shut Off and Opening a New Layer of the Bagong Well in the Lesma Field, In oil and gas exploitation activities at the Bg01 Well, the well has been in production for a long time, so there is a problem where the proportion of water content in production wells continues to  increase.  compared  to  the  proportion  of  oil  and  gas  content  produced,  the  improvement  is carried  out  using  the  water  shut  off  method  by  closing  the  existing  perforation  holes  and opening  new  perforations  in  the  same  layer.  Or  closing  the  existing  perforation  holes  that  are indicated to cause an increase in water and the production of other perforated parts. By closing the  layer,  it  is  hoped  that  the  water  cut  will  decrease  so  that  it  will  increase  oil  and  gas production.